(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study investigated schooling attitude and peer pressure as predictors of examination malpractice tendencies in Federal Unity College. A correlational research design was adopted for the study. No sampling was done as the entire population was used. The instruments used for the study are Schooling Attitude on Examination Malpractice Scale (SAEMS), Peer Pressure on Examination Malpractice Questionnaire (PPEMQ) and Examination Malpractice Tendency Inventory (EMTI). The instruments were face-validated using three experts and construct validated using factor analysis. The reliability indices of the instruments were ascertained to be 0.87, 0.87 and 0.90 using Cronbach alpha method for SAEMS, PPEMQ and EMTI, respectively. Linear and Multiple regression were used to answer the research questions using coefficient of determination (R2) value while the hypotheses were tested using ANOVA (regression output) at 0.05 level of significance. The result shows that schooling attitude and peer pressure are significant predictors of students` examination malpractice tendencies. The result equally shows that schooling attitude and peer pressure have a significant joint predictive power (80%, F= 918.020, p<0.05) on students` examination malpractice tendencies. The study recommends among others that workshops, seminars, conferences and sensitization trainings on the danger of examination malpractice tendencies should be organized for parents, teachers, students and the general public by the government in collaboration with examination bodies and educational stakeholders in order to create awareness on the menaces and dangers of examination malpractice tendencies. This could help reduce examination malpractice.